Assessment of quality of life in treated patients of cancer cervix - Zakia Rahman; Uma Singh; Sabuhi Qureshi; Nisha; Kirti Srivastav; Anil Nishchal (Wolters Kluwer Medknow Publications, 2017)
Aim: The aim of the study was to assess the quality of life (QoL) in women suffering from cancer cervix before and after the treatment, to study various factors affecting the QoL in these women, and to evaluate the impact of treatment modalities on the QoL. Materials and Methods: Women with cervical cancer attending Department of Obstetrics and Gynecology and Department of Radiotherapy who met the eligibility criteria were interviewed with a structured questionnaire of QoL, the European Organization for Research and Treatment of Cancer QLQ30, and its Cervical Cancer Module (Cx24). The baseline observations were recorded when the patient first reported, second evaluation was done at 3 months posttreatment, and the third evaluation at 6 months posttreatment. QoL domains along with sociodemographic and clinicopathological variables were analyzed. Results: A total of ninety patients were included for analysis, of which 5 were lost to follow up. A statistically significant improvement was found in physical, emotional function, pain, fatigue, and vaginal symptoms of the participants; however, there was no significant improvement in social, cognitive, or role functioning, body image, sexual activity, or sexual enjoyment. Vaginal and sexual function worsened significantly. Multivariate analysis showed that young women and those with a higher level of education had better QoL. Stage and type of cancer had little impact on the general QoL, but participants with earlier stage and well-differentiated cancer had better cancer cervix-specific QoL. Conclusion: The QoL of the participants in terms of physical (P = 0.04) and emotional functioning (P = 0.001) improved with treatment. Women with a higher level of education and early stage of disease had better QoL.